Parque urbano das tribos e circuito cultural sustentável: aproximação entre comunidade e território - Coutinho, Gabriel (2024)
The project "Urban Park of the Tribes and Sustainable Cultural Circuit" aims to promote sustainable development and preserve the culture of traditional communities, such as the indigenous people of the Tarumã-Açú neighborhood. These communities preserve ancestral traditions and the connection with nature in urban context. The proposal seeks to integrate the natural reserve into the territory occupied by residents since the 1980s, in line with the United Nations guidelines for inclusive, safe and sustainable cities. The intervention includes the creation of a Cultural, Commercial, Sports and Leisure Center, encouraging the community to approach its natural environment and promoting sustainability and cultural preservation.